Study on determinants of nutritional status of a school going children in a village of Tumakuru taluk - Mandolikar, Ravindra Y.; Jadhav, Smitha; Angadi, Mahabaleshwar Mahanthappa (International Journal Of Community Medicine And Public Health, 2019)
Background: Children (0-14 years) contribute to 26% of world population and 28.4% of India’s population. School going age is a formative period, physically as well as mentally, transferring child into a promising adult. Malnourishment in this age group compromises both physical and mental growth. The objective of the study was to assess the nutritional status and morbidity status among school going children. Methods: A cross sectional descriptive study was conducted at Greenberg international school Kannenahalli, Tumkur. After inclusion and exclusion criteria, which comprised children between 3-12 years of age, total 123 students were included in the study. A pre structured and pre tested proforma was used to collect the data on general information of the child, anthropometric measurements, physical examination, personal hygiene and clinical examination and blood grouping was done. Results: Out of 123 study participants, 30.9% were found to be malnourished and 35.77% had various morbidity conditions. Out of the 39 students who had malnutrition, 20 students (51.3%) were having grade 1 malnutrition, 15 students (38.5%) were having grade 2 malnutrition and 4 students (10.3%) were having grade 3 malnutrition. Conclusions: It concluded that, balanced diet for all the malnourished children to improve their nutritional status and also for healthy children to maintain their health and nutrition. Grade 3 malnourished children were referred to NRC (nutritional rehabilitation center) to improve their nutritional status.